Hearing Darius: A Bakhtinian Study of the Voice of Darius in the Behistun Inscription, Herodotus' The Histories, and Ezra-Nehemiah - Bowick, James E. (My University, 2010)
The theories of Bakhtin are becoming more influential in studies. The concepts of chronotope and polyphony have proved particularly useful in exploring narrative works. This thesis applies these concepts to the Behistun inscription, Herodotus' The Histories, and Ezra-Nehemiah to bring a more nuanced understanding to the character of Darius revealed in each work. The speeches of Darius, within their respective chronotopes and double-voiced by the narrator, reveal subtle undei10nes of characterization. In the Behistun inscription, the chronotope and the use of the monologic voice of Darius reveal a character lifted above the historical world to epic levels. In Herodotus, double voicing along with chronotope reveals Darius, who is otherwise presented as a powerful and mighty king, as vulnerable and human. In Ezra-Nehemiah, chronotope is used to raise Darius above the other Persian kings, except Cyrus, while double-voicing exposes his claim to be the true king of Israel through the support of the temple.
Keywords: Religion; Religion